THE DETERMINATION OF PHENOLS COMPOUNDS IN DISINFECTANTS - L. A. Nosikova; I. O. Melnikov; A. N. Kochetov (Тонкие химические технологии, 2017)
The aspects of analytical determination of disinfectants derivatives of the phenol series аrе considered. The possibility of codetermination of five derivatives of this series in different disinfectants using the RP-HPLC method in the isocratic mode (UV detection) is shown. Alternatively, the possibilities of the determination with the use of spectrophotometry and GC methods are considered. This study and previous ones showed that the extraction of phenol derivatives by organic solvents from а wide range of disinfectants is feasible only in some cases, preferably with the use of hexane as an extractant. Further spectrophotometry of hexane extracts does not always enable to correctly compensate for the effect of background impurities and requires an additional separation of the components. The literature data and experimental results suggest that it is more efficient to analyze the whole series of disinfectants in isopropanol (sometimes in water) by chromatographic methods, preferably by HPLC. Sample preparation reduces to the solubilization of batches of ready-made disinfectants in isopropanol/water. It is optimal to carry out the chromatographic study using elution with acetonitrile-based systems (for example, СН3СN:Н2O, 60:40) providing the correct determination (λ = 280 nт) of phenol derivatives. The completeness of extraction (if the extraction method is used), as well as the metrology aspects of all the analytical determination is set directly in а laboratory during the realization of procedures of introduction/validation according to the internal documents of the system quality management for the relevant structural unit.